Trigeminal Block for Submandibular Abscess in Pediatric with Difficult Intubation: A Case Report - Septian Adi Permana; Cipta, Juan (Indonesian Basic and Experimental Health Sciences, 2024)
Background: The use of trigeminal block with/without ultrasonography guidance as a pain management in outpatient settings are common, mainly for neuralgic pain. Whereas, the use of trigeminal block are not widely performed intraoperatively especially for oral-maxillofacial surgery. Case: We present a case of 16 year old boy diagnose with mandibular abscess prior to Open Reduction Internal Fixation (ORIF) due to mandibular fracture 1 months prior. Patient admitted with complaints of pain and swelling on right jaw, difficult opening his mouth and experienced a salty taste in mouth which we suspect the abscess penetrate into the oral cavity. Patient was in a limp condition, shortness of breath in supine position, with oxygen saturation of  96% room air. We use LEMON method to assess the intubation difficulties, we found swelling on the right jaw, Incisor distance less than 2 cm, make it impossible to evaluate mallampati score, and limited neck mobility due to pain. We decided to avoid general anesthesia since preoperative airway assessment indicates difficult intubation. We sedate the patient with midazolam and administered trigeminal block using 22-G needle with local anesthetic solution of levobupivacaine 0,375% and dexamethasone 2,5mg as an adjuvant with classic landmark trigeminal technique. The patient tolerated the procedure well and return to the ward after the procedure. Conclusion: The use of trigeminal block can be as an alternative general anesthesia oral-maxillofacial surgery area that may have predisposing difficult airway intubation and may be valuable in contributing better patients outcomes.